3D liver membrane system by co-culturing human hepatocytes, sinusoidal endothelial and stellate cells. (26th May 2017) - Ahmed, Haysam Mohamed Magdy; Salerno, Simona; Morelli, Sabrina; Giorno, Lidietta; De Bartolo, Loredana
Abstract: In this study, a designed approach has been utilized for the development of a 3D liver system. This approach makes use of primary human sinusoidal endothelial cells, stellate cells and hepatocytes that are seeded sequentially on hollow fiber membranes (HF) in order to mimic the layers of cells found in vivo . To this purpose modified polyethersulfone (PES) HF membranes were used for the creation of a 3D human liver system in static and dynamic conditions. In order to verify the positive effect of non-parenchymal cells on the maintenance of hepatocyte viability and functions, homotypic cultures of hepatocytes alone on the HF membranes were further investigated. The membrane surface allowed the attachment and self-assembly of the cells, forming tissue-like structures around and between fibers. Sinusoidal cells formed tube-like structures that surrounded hepatocytes organized in cords within aggregates promoted by stellate cells. The co-culture of hepatocytes with sinusoidal endothelial and hepatic stellate cells preserved structural architecture of the construct and improved the liver-specific functions. Most importantly, cells co-cultured in a HF membrane bioreactor synthesized albumin and urea for 28 days. The liver membrane bioreactor also preserved the drug biotransformation activity with a continuous production of diazepam phase I metabolites for an extended period of time. Additionally, the cell oxygen uptake rates highlighted the maintenance of the actual oxygen concentration at a level compatible with their metabolic functions.